Health Consequences of Environmental Exposures: Causal Thinking in Global Environmental Epidemiology - Peter D. Sly; David O. Carpenter; Martin Van den Berg; Renato T. Stein; Philip J. Landrigan; Marie-Noel; William Suk (Ubiquity Press, 2016)
The 2010 Global Burden of Disease estimates indicate a trend toward increasing years lived with disability from chronic noncommunicable diseases (NCDs). Risk factors examined included smoking, diet, alcohol, drug abuse, and physical inactivity. By contrast, little consideration was given to accumulating evidence that exposures to environmental chemicals, psychosocial stress, and malnutrition during fetal development and across the life span also increase risk of NCDs. To address this gap, we undertook a narrative review of early-life environmental contributions to disease. We documented numerous etiologicassociations. We propose that future GBD estimates use an expanded approach for assessing etiologic contributions of environmental exposures to recognized disease risk factors. We argue that broadening the definition of environmental disease, together with improved methods of assessing early life exposures and their health outcomes across the life span, will allow better understanding of causal associations and provide the incentives required to support strategies to control avoidable exposures and reduce disease risk.